Metrological-Characteristics-Based Calibration of Optical Areal Surface Measuring Instruments and Evaluation of Measurement Uncertainty for Surface Texture Measurements - Sai Gao; André Felgner; Uwe Brand (Instruments)
ISO 25178 part 600:2019 and part 700:2022 introduce a calibration framework based on seven metrological characteristics (MCs) for calibrating optical areal surface measuring instruments. Among these, topography fidelity is a newly defined metrological characteristic that remains a critical yet unresolved challenge in instrument calibration. This paper proposes strategies to address topography fidelity, including a key criterion for selecting suitable instrument setups by comparing slope measurement capability with local surface slopes, as well as methods for investigating the field-of-view homogeneity and directional performance difference along the x- and y-axes. Furthermore, the uncertainty contribution of topography fidelity in surface topography measurements is analysed. The paper also determines the uncertainty associated with the remaining six MCs. Based on the proposed MC-based calibration approach and the corresponding uncertainty contributions, an overall measurement uncertainty model for Sa and Sq parameters is presented. Finally, uncertainty evaluations for Sa and Sq are demonstrated on a challenging surface, where topography fidelity plays a significant role in the measurement uncertainty evaluation.